Extensional and shear rheology of okra polysaccharides in the presence of artificial saliva. (December 2018) - Yuan, Bo; Ritzoulis, Christos; Chen, Jianshe
Abstract Extensional and shear viscosities were studied for mixtures comprising artificial saliva and okra mucilage, the latter acting as a model thick-liquid food. These experiments aimed to obtain information on the flow-behavior information of the systems, underpinning the texture sensation of foods as perceived by dysphagic and xerostomic populations. Mixing okra mucilage with artificial saliva dramatically increases the shear viscosity of artificial saliva throughout the studied ranges of concentrations and deformation rates. Particle tracking does not suggest direct interactions between the components of artificial saliva and of okra mucilage. The rheology of the okra polymer (OP)–artificial saliva (AS) mixture is dominated by its extensional viscosity: Trouton ratios are in the order of tens to hundreds, while they decrease with increasing okra-mucilage concentration; this highlighs the dominance of the extensional rheology and the increasing importance of the shear mechanics with increasing okra content. The relaxation times and extensional moduli are also reported for the systems under study. Extensional and shear flows are of equal importance concerning the elastic behavior. Texture sensation: rheological data guide artificial saliva formulation Artificial saliva is usually formulated to help people with dysphagia or xerostomia. Their mouth feels of food textures are largely dependent on the flow behaviors of the food–artificial saliva mixtures. Christos Ritzoulis and coworkers from Zhejiang Gongshang University now studied the rheological and structural properties of artificial saliva when mixed with okra mucilage. They found the shear viscosity and storage modulus of the artificial saliva were much higher in the presence of okra polysaccharide, suggesting the formation of a macromolecular-interacting network. Moreover, it was found the overall rheological behaviors of the mixtures were always dominated by the extensional viscosity, though the shear behavior became more and more obvious with the increasing amount of okra polymer. Together with the data obtained with real saliva, these on artificial saliva could guide the future formulation of artificial saliva.